Effectiveness of the STAD Technique in Sakubun Teaching in Indonesia - Latif Jaohari, Abdul; Ariestafuri, Dinda, Nurza; Ranadireksa, Gayatri (International Journal of Psychosocial Rehabilitation, 2020)
Writing cannot be separated from the world of education. Writing skills are absolutely necessary for academic staff who are involved in the world of education. However, the reality today, including what the researchers feel while learning languages, is that writing skills are indeed something that is difficult and seems least desirable. There are many factors behind this, whether it is a mistake in learning to write or the failure of teaching writing in Indonesia is generally caused by the inappropriate way of teaching writing in school. The theories given by the instructor to his students do not help much to develop the task of writing. Thus, most severely when the instructor himself feels troubled by the task of correcting, the students' writings and assignments are not returned. The word “sakubun” in the Kenji Matsura dictionary is translated as writing an essay. According to Marwoto (1998), composing is a person's ability to tell his life experience in written language that is clear, coherent, expressive, readable, and can be understood by others. Writing is an activity of expressing ideas in writing. One of the functions of the Sakubun lesson is the development of reasoning (Tarigan, 1995). In addition, composing is an activity to express opinions, ideas, knowledge, and life experiences through written language in the form of graphic symbols so that the meaning can be understood by others.